STATUS OF WASH IN RURAL HEALTH FACILITIES OF DISTRICT BAGH, AZAD KASHMIR: A CROSS-SECTIONAL OBSERVATIONAL STUDY - Sehar, Bismillah; Yaqoob, Muhammad; Hanif, Asif; Ali Saad R. Alsubaie; Zeb, Falak (Journal of Ayub Medical College Abbottabad, 2021)
Background: Water, sanitation, and hygiene (WASH) practices play vital role for ensuring quality of health care with the prevention of infections. Low- and middle-income health care settings have very limited WASH services and practices. Pakistan is still fighting with the burden of communicable diseases that can be prevented by health education on WASH services and their practices which is the elementary requirement for achieving national developing targets. Methods: This was the cross-sectional study conducted at 10 rural health centres (RHCs) of district Bagh by using purposive sampling technique. The duration of the study was 3 months from March to May, 2020. The tool used for the assessment of WASH services and practices was WASH FIT (Water Sanitation for Health Facility Improvement Tool) by WHO which had three categories for assessment in five different domains. Results: The findings showed that none of the facility was meeting the national standards of water quality. 50% of the facilities had separate male and female toilets while none of them have managed the menstrual hygiene needs. Only 10% of toilets facilitates the people with limited and reduce mobility. Only 10% of the facilities had well trained personal for health care waste management. None of the facility had or provided suitable protective measures for the waste management personals. Hand hygiene compliance activities were in 40% of the facilities. Conclusion: The improvement of WASH in health care centres plays a fundamental role in the prevention of infections, but none of them had WASH assessment tools to monitor the status of WASH.